ADSORPTION OF FE METAL ION IN SOLUTION USING NATURAL ZEOLITE ACTIVATED BY KOH - Palentin, Ersa Rizkita; Hindryawati, Noor; Gunawan, Rahmat (JURNAL ATOMIK, 2019)
Adsorbtion of Fe metal ion in solution using natural zeolite activated by KOH has been conducted. Natural zeolite was characterized using X-Ray Flourescence (XRF), X-Ray Diffraction (XRD) and surface area test. The XRF analysis results showed a decreasing SiO2 composition in natural zeolite activated by KOH 1.5 M. XRD analysis results showed the type of natural zeolite activated by KOH was mordenite with the chemical compound Ca2.5Na2Al7Si41O96.24H2O. The surface area of natural zeolite was 75.041 m2/g and after activation with KOH 1.5 M was 126.908 m2/g. The optimum conditions for the adsorption of Fe ions was at pH 4 with % adsorption was 96.24% at a 90 minutes the % adsorption was 98.3%.